equivalent expressions - math

I'm trying to figure out an equivalent expressions of the following equations using bitwise, addition, and/or subtraction operators. I know there's suppose to be an answer (which furthermore generalizes to work for any modulus 2^a-1, where a is a power of 2), but for some reason I can't seem to figure out what the relation is.
Initial expressions:
x = n % (2^32-1);
c = (int)n / (2^32-1); // ints are 32-bit, but x, c, and n may have a greater number of bits
My procedure for the first expression was to take the modulo of 2^32, then try to make up the difference between the two modulo's. I'm having trouble on this second part.
x = n & 0xFFFFFFFF + difference // how do I calculate difference?
I know that the difference n%(2^32)-n%(2^32-1) is periodic (with a period of 2^32*(2^32-1)), and there's a "spike up' starting at multiples of 2^32-1 and ending at 2^32. After each 2^32 multiple, the difference plot decreases by 1 (hopefully my descriptions make sense)
Similarly, the second expression could be calculated in a similar fashion:
c = n >> 32 + makeup // how do I calculate makeup?
I think makeup steadily increases by 1 at multiples of 2^32-1 (and decreases by 1 at multiples of 2^32), though I'm having troubles expressing this idea in terms of the available operators.

You can use these identities:
n mod (x - 1) = (((n div x) mod (x - 1)) + ((n mod x) mod (x - 1))) mod (x - 1)
n div (x - 1) = (n div x) + (((n div x) + (n mod x)) div (x - 1))
First comes from (ab+c) mod d = ((a mod d) (b mod d) + (c mod d)) mod d.
Second comes from expanding n = ax + b = a(x-1) + a + b, while dividing by x-1.

I think I've figured out the answer to my question:
Compute c first, then use the results to compute x. Assumes that the comparison returns 1 for true, 0 for false. Also, the shifts are all logical shifts.
c = (n>>32) + ((t & 0xFFFFFFFF) >= (0xFFFFFFFF - (n>>32)))
x = (0xFFFFFFFE - (n & 0xFFFFFFFF) - ((c - (n>>32))<<32)-c) & 0xFFFFFFFF
edit: changed x (only need to keep lower 32 bits, rest is "junk")

Related

How to convert a bitstream to a base20 number?

Given is a bitstream (continuous string of bits too long to be processed at once) and the result should be a matching stream of base20 numbers.
The process is simple for a small number of bits:
Assuming most significant bit right:
110010011 = decimal 403 (1 * 1 + 1 * 2 + 1 * 16 + 1 * 128 + 1 * 256)
403 / 20 = 20 R 3
20 / 20 = 1 R 0
1 / 20 = 0 R 1
Result is [3, 0, 1] = 3 * 1 + 0 * 20 + 1 * 400
But what if the bits are too much to be converted to a decimal number in one step?
My approach was doing both processes in a loop: Convert the bits to decimal and converting the decimal down to base20 numbers. This process requires the multipliers (position values) to be lowered while walking through the bits, because otherwise, they'll quickly increase too much to be calculated probably. The 64th bit would have been multiplied by 2^64 and so on.
note: I understood the question that a bitstream is arriving of unknown length and during an unknown duration and a live conversion from base 2 to base 20 should be made.
I do not believe this can be done in a single go. The problem is that base 20 and base 2 have no common ground and the rules of modular arithmetic do not allow to solve the problem cleanly.
(a+b) mod n = ( (a mod n) + (b mod n) ) mod n
(a*b) mod n = ( (a mod n) * (b mod n) ) mod n
(a^m) mod n = ( (a mod n)^m ) mod n
Now if you have a number A written in base p and q (p < q) as
A = Sum[a[i] p^i, i=0->n] = Sum[b[i] q^i, i=0->n]
Then we know that b[0] = A mod q. However, we do not know A and hence, the above tells us that
b[0] = A mod q = Sum[a[i] p^i, i=0->n] mod q
= Sum[ (a[i] p^i) mod q, i=0->n] mod q
= Sum[ ( (a[i] mod q) (p^i mod q) ) mod q, i=0->n] mod q
This implies that:
If you want to know the lowest digit b0 of a number in base q, you need to have the knowledge of the full number.
This can only be simplified if q = pm as
b[0] = A mod q = Sum[a[i] p^i, i=0->n] mod q
= Sum[ (a[i] p^i) mod q, i=0->n] mod q
= Sum[ a[i] p^i, i=0->m-1]
So in short, since q = 20 and p = 2. I have to say, no, it can not be done in a single pass. Furthermore, remind yourself that I only spoke about the first digit in base q and not yet the ith digit.
As an example, imagine a bit stream of 1000 times 0 followed by a single 1. This resembles the number 21000. The first digit is easy, but to get any other digit ... you are essentially in a rather tough spot.

Is it safe to replace "a/(b*c)" with "a/b/c" when using integer-division?

Is it safe to replace a/(b*c) with a/b/c when using integer-division on positive integers a,b,c, or am I at risk losing information?
I did some random tests and couldn't find an example of a/(b*c) != a/b/c, so I'm pretty sure it's safe but not quite sure how to prove it.
Thank you.
Mathematics
As mathematical expressions, ⌊a/(bc)⌋ and ⌊⌊a/b⌋/c⌋ are equivalent whenever b is nonzero and c is a positive integer (and in particular for positive integers a, b, c). The standard reference for these sorts of things is the delightful book Concrete Mathematics: A Foundation for Computer Science by Graham, Knuth and Patashnik. In it, Chapter 3 is mostly on floors and ceilings, and this is proved on page 71 as a part of a far more general result:
In the 3.10 above, you can define x = a/b (mathematical, i.e. real division), and f(x) = x/c (exact division again), and plug those into the result on the left ⌊f(x)⌋ = ⌊f(⌊x⌋)⌋ (after verifying that the conditions on f hold here) to get ⌊a/(bc)⌋ on the LHS equal to ⌊⌊a/b⌋/c⌋ on the RHS.
If we don't want to rely on a reference in a book, we can prove ⌊a/(bc)⌋ = ⌊⌊a/b⌋/c⌋ directly using their methods. Note that with x = a/b (the real number), what we're trying to prove is that ⌊x/c⌋ = ⌊⌊x⌋/c⌋. So:
if x is an integer, then there is nothing to prove, as x = ⌊x⌋.
Otherwise, ⌊x⌋ < x, so ⌊x⌋/c < x/c which means that ⌊⌊x⌋/c⌋ ≤ ⌊x/c⌋. (We want to show it's equal.) Suppose, for the sake of contradiction, that ⌊⌊x⌋/c⌋ < ⌊x/c⌋ then there must be a number y such that ⌊x⌋ < y ≤ x and y/c = ⌊x/c⌋. (As we increase a number from ⌊x⌋ to x and consider division by c, somewhere we must hit the exact value ⌊x/c⌋.) But this means that y = c*⌊x/c⌋ is an integer between ⌊x⌋ and x, which is a contradiction!
This proves the result.
Programming
#include <stdio.h>
int main() {
unsigned int a = 142857;
unsigned int b = 65537;
unsigned int c = 65537;
printf("a/(b*c) = %d\n", a/(b*c));
printf("a/b/c = %d\n", a/b/c);
}
prints (with 32-bit integers),
a/(b*c) = 1
a/b/c = 0
(I used unsigned integers as overflow behaviour for them is well-defined, so the above output is guaranteed. With signed integers, overflow is undefined behaviour, so the program can in fact print (or do) anything, which only reinforces the point that the results can be different.)
But if you don't have overflow, then the values you get in your program are equal to their mathematical values (that is, a/(b*c) in your code is equal to the mathematical value ⌊a/(bc)⌋, and a/b/c in code is equal to the mathematical value ⌊⌊a/b⌋/c⌋), which we've proved are equal. So it is safe to replace a/(b*c) in code by a/b/c when b*c is small enough not to overflow.
While b*c could overflow (in C) for the original computation, a/b/c can't overflow, so we don't need to worry about overflow for the forward replacement a/(b*c) -> a/b/c. We would need to worry about it the other way around, though.
Let x = a/b/c. Then a/b == x*c + y for some y < c, and a == (x*c + y)*b + z for some z < b.
Thus, a == x*b*c + y*b + z. y*b + z is at most b*c-1, so x*b*c <= a <= (x+1)*b*c, and a/(b*c) == x.
Thus, a/b/c == a/(b*c), and replacing a/(b*c) by a/b/c is safe.
Nested floor division can be reordered as long as you keep track of your divisors and dividends.
#python3.x
x // m // n = x // (m * n)
#python2.x
x / m / n = x / (m * n)
Proof (sucks without LaTeX :( ) in python3.x:
Let k = x // m
then k - 1 < x / m <= k
and (k - 1) / n < x / (m * n) <= k / n
In addition, (x // m) // n = k // n
and because x // m <= x / m and (x // m) // n <= (x / m) // n
k // n <= x // (m * n)
Now, if k // n < x // (m * n)
then k / n < x / (m * n)
and this contradicts the above statement that x / (m * n) <= k / n
so if k // n <= x // (m * n) and k // n !< x // (m * n)
then k // n = x // (m * n)
and (x // m) // n = x // (m * n)
https://en.wikipedia.org/wiki/Floor_and_ceiling_functions#Nested_divisions

Numerically stable evaluation of sqrt(x+a) - sqrt(x)

Is there an elegant way of numerically stable evaluating the following expression for the full parameter range x,a >= 0?
f(x,a) = sqrt(x+a) - sqrt(x)
Also is there any programming language or library that does provide this kind of function? If yes, under what name? I have no specific problem using the above expression right now, but encountered it many times in the past and always thought that this problem must have been solved before!
Yes, there is! Provided that at least one of x and a is positive, you can use:
f(x, a) = a / (sqrt(x + a) + sqrt(x))
which is perfectly numerically stable, but hardly worth a library function in its own right. Of course, when x = a = 0, the result should be 0.
Explanation: sqrt(x + a) - sqrt(x) is equal to (sqrt(x + a) - sqrt(x)) * (sqrt(x + a) + sqrt(x)) / (sqrt(x + a) + sqrt(x)). Now multiply the first two terms to get sqrt(x+a)^2 - sqrt(x)^2, which simplifies to a.
Here's an example demonstrating the stability: the troublesome case for the original expression is where x + a and x are very close in value (or equivalently when a is much smaller in magnitude than x). For example, if x = 1 and a is small, we know from a Taylor expansion around 1 that sqrt(1 + a) should be 1 + a/2 - a^2/8 + O(a^3), so sqrt(1 + a) - sqrt(1) should be close to a/2 - a^2/8. Let's try that for a particular choice of small a. Here's the original function (written in Python, in this case, but you can treat it as pseudocode):
def f(x, a):
return sqrt(x + a) - sqrt(x)
and here's the stable version:
def g(x, a):
if a == 0:
return 0.0
else:
return a / ((sqrt(x + a) + sqrt(x))
Now let's see what we get with x = 1 and a = 2e-10:
>>> a = 2e-10
>>> f(1, a)
1.000000082740371e-10
>>> g(1, a)
9.999999999500001e-11
The value we should have got is (up to machine accuracy): a/2 - a^2/8 - for this particular a, the cubic and higher order terms are insignificant in the context of IEEE 754 double-precision floats, which only provide around 16 decimal digits of precision. Let's compute that value for comparison:
>>> a/2 - a**2/8
9.999999999500001e-11

How to set a square root to only be whole

I cant seem to find any kind of answer to this, but if I have an equation like the square root of (X^2-4n) where 4n is a constant, how could I set x so the equation gives a whole number.
I know setting x to n+1 works, but I'm looking for an algorithm that would generate all solutions.
So, the problem is to find all pairs of integers (x, m) such that:
sqrt(x^2 - 4n) = m
We have:
x^2 - 4n = m^2
or
x^2 - mˆ2 = 4n
so
(x + m)(x - m) = 4n
Now, 2 divides 4n and so it must divide (x+m) or (x-m). But if it divides any of them it will divide the other too. Thus a := (x+m)/2 and b := (x-m)/2 are both integers. Therefore
a*b = n
So, it is just a matter of factoring n as a*b in all possible ways and recover x and m from the equations above:
x = a + b.
m = a - b.
Your solution x = n+1 corresponds to the trivial factorization n = n*1 where a=n and b=1.
UPDATE
Here is an algorithm that prints all pairs (x, m)
[Initialize] a := n.
[Check] if n % a = 0 then
b := n / a.
print(a + b), print(a - b)
[Decrement] a := a - 1.
[End?] if a * a > n go to Step 2.

Can someone explain Mathematical Induction (to prove a recursive method)

Can someone explain mathematical induction to prove a recursive method? I am a freshmen computer science student and I have not yet taken Calculus (I have had up through Trig). I kind of understand it but I have trouble when asked to write out an induction proof for a recursive method.
Here is a explanation by example:
Let's say you have the following formula that you want to prove:
sum(i | i <- [1, n]) = n * (n + 1) / 2
This formula provides a closed form for the sum of all integers between 1 and n.
We will start by proving the formula for the simple base case of n = 1. In this case, both sides of the formula reduce to 1. This in turn means that the formula holds for n = 1.
Next, we will prove that if the formula holds for a value n, then it holds for the next value of n (or n + 1). In other words, if the following is true:
sum(i | i <- [1, n]) = n * (n + 1) / 2
Then the following is also true:
sum(i | i <- [1, n + 1]) = (n + 1) * (n + 2) / 2
To do so, let's start with the first side of the last formula:
s1 = sum(i | i <- [1, n + 1]) = sum(i | i <- [1, n]) + (n + 1)
That is, the sum of all integers between 1 and n + 1 is equal to the sum of integers between 1 and n, plus the last term n + 1.
Since we are basing this proof on the condition that the formula holds for n, we can write:
s1 = n * (n + 1) / 2 + (n + 1) = (n + 1) * (n + 2) / 2 = s2
As you can see, we have arrived at the second side of the formula we are trying to prove, which means that the formula does indeed hold.
This finishes the inductive proof, but what does it actually mean?
The formula is correct for n = 0.
If the formula is correct for n, then it is correct for n + 1.
From 1 and 2, we can say: if the formula is correct for n = 0, then it is correct for 0 + 1 = 1. Since we proved the case of n = 0, then the case of n = 1 is indeed correct.
We can repeat this above process again. The case of n = 1 is correct, then the case of n = 2 is correct. This reasoning can go ad infinitum; the formula is correct for all integer values of n >= 1.
induction != Calc!!!
I can get N guys drunk with 10*N beers.
Base Case: 1 guy
I can get one guy drunk with 10 beers
Inductive step, given p(n) prove p(n + 1)
I can get i guys drunk with 10 * i beers, if I add another guy, I can get him drunk with 10 more beers. Therefore, I can get i + 1 guys drunk with 10 * (i + 1) beers.
p(1) -> p(i + 1) -> p(i + 2) ... p(inf)
Discrete Math is easy!
First, you need a base case. Then you need an inductive step that holds true for some step n. In your inductive step, you will need an inductive hypothesis. That hypothesis is the assumption that you needed to have made. Finally, use that assumption to prove step n+1

Resources